Analysis and Modeling of Thermal Effect and Optical Characteristic of LED Systems With Parallel Plate-Fin Heatsink - Huanting Chen; Shuo Lin; Chuanbing Xiong (IEEE Photonics Journal, 2017)
Based on the photoelectrothermal (PET) theory, prediction methods for the thermal effect and optical properties of the light-emitting diode (LED) systems mounted on a given parallel plate-fin heatsink are proposed in this paper. With the PET theory and the heatsink characteristics (heat transfer coefficient, equivalent radius for heat source, fins efficiency), it is possible to accurately quantify junction temperature, heat dissipation coefficient, optical power, and luminous flux of the LED systems. The prediction model consists of a series of optical and thermal evaluation, with which it is simple for LED system designers to comply. The proposed model has been validated using LED sources, which shows good agreement between the calculated and experimental results.